Analysis of food price movement in Nigeria: Focus on price behaviour in Oyo State - LADIPO , O. O.; OLUDIMU, O. L. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
Market prices for rice, maize and gari, which account for 70% of the food commodities traded and consumed in Oyo State of Nigeria, were analysed for the period, 1968-1981. Retail market prices were found to follow a rapidly increasing trend. This led to a quantitative assessment of the probable influences on price changes: Results on such influences show that last season's (immediate past) prices and the quantity of money supply (evidenced in per capita current income) have a major influence on the current level of prices. On this basis, policy recommendations were made with respect to satisfying consumers' demand especially regarding effort to make staple foods available at the right time and at reasonable prices.